Study of the Effects of Changing Physiological Conditions on Dielectric Properties of Breast Tissues. (30th July 2013) - Sabouni, Abas; Hahn, Camerin; Noghanian, Sima; Sauter, Edward; Weiland, Tim
Abstract : This paper addresses the changes in the physical characteristics (temperature and water/blood content) of breast tissue under different physiological conditions. We examined ex vivo specimens of breast tissue excised at the time of surgery to study the effects of physiological conditions on dielectric properties. We observed that the dielectric properties strongly depend on tissue physiological state. When the biological tissues undergo physiological changes, such as those due to disease or those induced by external changes such as variations in the environmental temperature, the microscopic processes deviate from their normal state and impact the overall dielectric properties. This suggests that microwave imaging might be used to monitor the physiological conditions of the body.